Sense of Balance in Indian Conceptualisation of Psychological Well-being - Joseph Jeyaraj Swaminathan; Giuseppe Crea; Zbigniew Formella (Studia Ecologiae et Bioethicae)
The concept of psychological well-being (PWB) engages the attention of those who live in the Global North, as well as those in the Global South. Similar to the Western concept of PWB, its Indian conceptualisation too, has a long history dating back to at least 3,000 years. This article accentuates that, in India, a ‘sense of balance’ (sama in Sanskrit) is an overarching principle that guides ecological, social, and personal well-being. This sense of balance is discussed in the exposition of concepts, such as hedonia and eudaimonia, which are found in both the Western and Indian concept of PWB. Major differences include the collectivist nature of Indians, their emphasis of spirituality and their belief that suffering and happiness are two dimensions of a single reality. Through a comparative narrative method, it is evidenced that Indian constructs, namely, Sama, Dharma, Sattva, Rajas and Tamas resonate meaningfully with universal principles, such as ethical living, social commitment, and spiritual awareness. In short, Indian conceptualisation of PWB holds that it is holistic, integrated, and balanced. An extended prospect of this sense of balance is its appropriateness in enabling people to achieve ecological balance, irrespective of their cultural affiliations.